2006
DOI: 10.2174/138161206777698756
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Inhibitors: Perspectives for Medical, Surgical and Radiation Oncology

Abstract: In the past decade, many angiogenesis inhibitors have been developed for clinical use in oncology. Surgeons, radiotherapists as well as medical oncologists have been investigating with much effort and enthusiasm the translation of these agents from the preclinical setting into treatment strategies of patients. Recently, for the first time in history, the angiogenesis inhibitor bevacizumab (avastin), a humanized anti-vascular endothelial growth factor (VEGF) antibody, showed a survival benefit of 4.7 months in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 67 publications
(74 reference statements)
1
34
0
Order By: Relevance
“…Therefore, rmES treatment induces cell death rather than inhibiting cell proliferation, suggesting that ES treatment is more suitable as adjuvant therapy or in combination with RT. Results of this study confirm those of previous studies and demonstrate that rmES potentiates the cytotoxic effects of RT (5,6,(27)(28)(29)(30). Of note, however, is that the results do not indicate the benefits of combination therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, rmES treatment induces cell death rather than inhibiting cell proliferation, suggesting that ES treatment is more suitable as adjuvant therapy or in combination with RT. Results of this study confirm those of previous studies and demonstrate that rmES potentiates the cytotoxic effects of RT (5,6,(27)(28)(29)(30). Of note, however, is that the results do not indicate the benefits of combination therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of various studies have shown that the addition of anti-angiogenic agents to RT increases clinical efficacy (5). Reports have suggested that ES may effectively enhance the effects of RT for tumor cells in vitro (3,6).…”
Section: Introductionmentioning
confidence: 99%
“…After cooling, the resulting precipitate was collected by filtration and washed with ethanol. The crude product was suspended in water (elimination of NH 4 3-Chlorophenyl 6-hexamethylenetetrammoniomethyl-2-oxo-2H-1-benzopyran-3-carboxylate chloride salt (26c) was obtained as described for 26a after the reaction of hexamethylenetetramine (1.8 g, 12.8 mmol) with 3-chlorophenyl 6-chloromethyl-2-oxo-2H-1-benzopyran-3-carboxylate (25c) (2 g, 5.7 mmol). The resulting precipitate was collected by filtration and washed with cold CHCl 3 : mp 210°C.…”
Section: -Fluorophenyl 6-nitro-2-oxo-2h-1-benzopyran-3-carboxylate (mentioning
confidence: 99%
“…Indeed, many efforts are now focussed on the search of compounds interfering with the cancer cell invasion process and expressing antiangiogenic properties [1]. Examples of drugs, among which monoclonal antibodies and small molecules, are currently under clinical investigation and some of them have recently been approved for use in man in the treatment of several cancers associated or not with conventional chemotherapies or radiation therapies [2][3][4][5][6][7][8][9]. These drugs comprise vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF) inhibitors (monoclonal antibodies) as well as VEGF and EGF receptor tyrosine kinase inhibitors (small-molecule inhibitors), but also matrix metalloproteinase (MMP), urokinase (uPA), cycloogygenase-2 (COX-2) or methionine aminopeptidase inhibitors [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation